2019
DOI: 10.1109/access.2019.2947738
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Quantum Radar Cross Section for Electrically Large Targets With GPU

Abstract: As an extension of traditional radar, quantum radar has the advantages of enhancing detection capability and improving resolution, which has attracted enormous attentions. However, the researches on the scattering characteristics of quantum radar are limited to two-dimensional targets, impeding the practical applications of quantum radar. In this paper, the universal expression of quantum radar cross section (QRCS) for three-dimensional targets is introduced. We have demonstrated the achievement of largescale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Since the aim is to verify the new approach by comparing it with the simulated and published results [5], [12], and [13], for this reason, a simple geometric shape is selected. There are some numerical and theoretical modeling of RCS for a metal square plate [5], [13], [21]. The simulated result in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the aim is to verify the new approach by comparing it with the simulated and published results [5], [12], and [13], for this reason, a simple geometric shape is selected. There are some numerical and theoretical modeling of RCS for a metal square plate [5], [13], [21]. The simulated result in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our purpose is to utilize MoM with the current density operator to compute the scattering field and the related RCS. It is shown that using the current density operator [7], [18] in QMoM gives us some degree of freedom ignored in the classical picture, CRCS, in which the average of the current density has been employed [5]. We want to show by QMoM that using dipole approximation to calculate RCS is not a complete method.…”
Section: A Canonical Quantization Methods To Derive the Scattering Phmentioning
confidence: 99%
See 3 more Smart Citations